The Use of AI-based Virtual Assistant to Support Islamic Religious Education and Digital Literacy in Labschool Elementary School (Current Research in Education: Conference Series Journal, 2024)
This study aimed to assess the implementation of an artificial intelligence-based virtual assistant to support Islamic religious education and enhance digital literacy at Labschool Elementary School. The research employed a comprehensive approach, including literature review, system design, virtual assistant development, simulation implementation, and evaluation. The virtual assistant, named SchoolPal, was meticulously developed and integrated with the advanced GPT-4-32K model on the Telegram platform. The evaluation of SchoolPal's performance revealed its remarkable ability to deliver accurate and relevant responses across a wide range of questions. Moreover, students at Labschool Elementary School demonstrated a noticeable improvement in their understanding after engaging with SchoolPal. The findings highlight the tremendous potential of this artificial intelligence-based virtual assistant in effectively supporting and enriching the learning experience at Labschool Elementary School.